STUDENTS’ PARTICIPATION IN MANAGING OF HIGHER EDUCATIONAL ESTABLISHMENTS WITHIN THE UNIVERSITY AUTONOMY - Hubina, Alla M. (Educological discourse, 2015)
The article deals with the concept of university autonomy, its interpretation in European education system and in Ukraine at different periods of the universities’ existence. The peculiarities of students’ influence on their learning environment in European universities are shown. Lutsk NTU students' understanding of the idea of the university autonomy and participation of students in the life of an autonomous university are analyzed. Prospects of improving of university life through involvement of students in the operation of the university through students’ self-government are determined.